Pembelajaran Fiqih Melalui Model Pembelajaran Kooperatif Tipe Co-op Co-op Untuk Meningkatkan Prestasi Siswa Pada Pokok Bahasan Shalat - Peri Ramdani; Mohamad Yudiyanto; Mulyana, Jajang (Prodi PGMI STAI Sabili Bandung, 2022)
Student achievement in learning fiqh is still considered low. This is partly because teachers in schools tend to use conventional learning which makes students passive in learning. Therefore, a research is needed that can overcome these problems. Cooperative learning is an alternative in improving student achievement. This study uses an experimental method with a quasi-experimental design in the form of a non-equivalent control group design so that there are 2 classes with 1 experimental class and 1 control class. The experimental class I used Co-op Co-op type of cooperative learning, the experimental class II used conventional learning. The purpose of this study was to determine: (a) the activities of teachers and students using Co-op Co-op and Conventional Co-op learning; (b) differences in student achievement (cognitive) using Co-op and Conventional Co-op learning; (c) Knowing students' attitudes (affective) towards Co-op Co-op type of cooperative learning; (d) knowing the student's (psychomotor) activity towards Co-op Co-op type of cooperative learning. The results of the study are as follows: (a) The percentage of the implementation of teacher and student activities using Co-op Co-op type of cooperative learning at the first meeting is 45.46%, the second meeting is 72.73% and the third meeting is 72.73%. (b) There is a difference in the increase in student achievement (cognitive) between those using Co-op Co-op type of cooperative learning and conventional learning. (c) The attitude of students (affective) who use Co-op Co-op type of cooperative learning is positive. (d) Student activity (psychomotor) using Co-op Co-op type of cooperative learning has an influence in improving the quality of students' prayer practices.